2004
DOI: 10.1080/09712119.2004.9706515
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous or Rotational Grazing on Goat Diets in a Desert Rangeland

Abstract: Mellado, M., Olvera, A., Dueiiez, J. and Rodriguez, A. 2004

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
5
12
1
Order By: Relevance
“…Grass use by goats in our study was several times larger than that reported in shrubdominated plant communities in arid zones (Sidahmed et al, 1981;Mellado et al, 1991Mellado et al, , 2003Mellado et al, , 2004, which reaffirms that goats are very flexible with the vegetation classes they consume. On the other hand, forbs utilization by goats in the present study was much lower than noted in other studies in the same environmental conditions (Mellado et al, 2003(Mellado et al, , 2004.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Grass use by goats in our study was several times larger than that reported in shrubdominated plant communities in arid zones (Sidahmed et al, 1981;Mellado et al, 1991Mellado et al, , 2003Mellado et al, , 2004, which reaffirms that goats are very flexible with the vegetation classes they consume. On the other hand, forbs utilization by goats in the present study was much lower than noted in other studies in the same environmental conditions (Mellado et al, 2003(Mellado et al, , 2004.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, forbs utilization by goats in the present study was much lower than noted in other studies in the same environmental conditions (Mellado et al, 2003(Mellado et al, , 2004.…”
Section: Discussioncontrasting
confidence: 82%
“…On the other hand, reduced DMI with increasing levels of S. elaeagnifolium in the diet may also be a result of comparatively lower energy concentration and OM digestibility of S. elaeagnifolium, compared to alfalfa hay. However, previous research has shown that, under range conditions, goats readily select and consume S. elaeagnifolium (up to one-third of the diet; Mellado et al, 2004). It is possible that selective foraging behavior allows grazing goats to select plant material lower in PSC than encountered on average in the plant biomass.…”
Section: Feeding Trialmentioning
confidence: 97%
“…Despite of its toxicity, S. elaeagnifolium can become in certain seasons the most important component of the diet of goats on degraded rangelands in northern Mexico (Mellado et al, 2003(Mellado et al, , 2004, apparently without clinical toxicity effects (Boyd et al, 1984). Typical for most range plants and especially noxious weeds, despite their importance for the diets of free grazing ruminants, no nutritional information is available for S. elaeagnifolium.…”
Section: Introductionmentioning
confidence: 98%
“…Ricardi and Shimada 1992;Dziba et al 2003); * age and body condition (more shrub consumed by adults compared with juveniles in the rainy season, and by goats in lower body condition; Mellado et al 2004b); * grazing management system (more shrub consumed under rotational than continuous grazing; Mellado et al 2004c); and * reproductive status (more forbs and grasses consumed by pregnant or lactating does, according to nutritional requirements; Mellado et al 2005). While a preference for shrubs has generally been found, several exceptions have been reported.…”
Section: Diet Selectionmentioning
confidence: 99%